2008
DOI: 10.1017/s000711450787231x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ramadan fasting on some indices of insulin resistance and components of the metabolic syndrome in healthy male adults

Abstract: The purpose of the present study was to evaluate the effect of Ramadan fasting on insulin sensitivity in subjects with the metabolic syndrome. Males (n 55; age 34·1 (SD 8·9) years) with the metabolic syndrome were studied. Blood pressure, waist circumference, body weight, HDL-cholesterol (HDL-C), TAG, fasting plasma glucose (FPG), fasting blood insulin and insulin resistance indices (quantitative insulin sensitivity check index (QUICKI), homeostasis model assessment of insulin resistance (HOMA-IR) and reciproc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 23 publications
6
58
2
Order By: Relevance
“…Regarding insulin sensitivity, our results in healthy subjects are in line with the findings of Bahijri et al obtained in healthy subjects (10), with the findings of Shariatpanahi et al obtained in subjects with metabolic syndrome (18), with the findings of Unalacak et al obtained in nonobese healthy male subjects (24), and with the results of Yarahmadi et al in patients with type 2 diabetes (19).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding insulin sensitivity, our results in healthy subjects are in line with the findings of Bahijri et al obtained in healthy subjects (10), with the findings of Shariatpanahi et al obtained in subjects with metabolic syndrome (18), with the findings of Unalacak et al obtained in nonobese healthy male subjects (24), and with the results of Yarahmadi et al in patients with type 2 diabetes (19).…”
Section: Discussionsupporting
confidence: 93%
“…Shariatpanahi et al found that Ramadan fasting is associated with improvement in insulin sensitivity (1/HOMA-IR) in patients with metabolic syndrome (18). Yarahmadi et al described that insulin resistance significantly decreased during Ramadan fasting in patients with type 2 diabetes (19).…”
Section: Discussionmentioning
confidence: 99%
“…Another survey showed a downward trend in second week of Ramadan in comparison to baseline, however, it increased significantly after Ramadan (8). Similar results have been reported about normal controls in Jordan, while other studies have attributed the weight loss during Ramadan to lower calorie intake (16,17). It is possible that the weight loss is due to the efficient utilization of body fat during fasting.…”
Section: Body Weight and Body Mass Indexsupporting
confidence: 87%
“…Adult men with the metabolic syndrome were studied during this month, in which 58% of their TEI was consumed in the evening. 106 Self-reported TEI was reduced by ≈56 kcal/d, and body weight and waist circumference decreased by 2.4% during the month of Ramadan. Fasting plasma glucose and systolic and diastolic blood pressures decreased, and HDL cholesterol and insulin sensitivity increased, but fasting plasma insulin, triglycerides, and HOMA-IR did not change.…”
Section: Meal Timing and Cardiometabolic Risk: Clinical Intervention mentioning
confidence: 92%